2020
DOI: 10.3390/ma13061276
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Variability of Plastic CTOD

Abstract: This paper presents a numerical study on the influence of material parameters and loading variability in the plastic crack tip opening displacement (CTOD) results. For this purpose, AA7050-T6 was selected as reference material and a middle-cracked tension specimen geometry was considered. The studied input parameters were the Young’s modulus, Poisson’s ratio, isotropic and kinematic hardening parameters and the maximum and minimum applied loads. The variability of the input parameters follows a Gaussian distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On previous works, the authors obtained numerical results in good agreement with experimental data, considering the cyclic plastic strain at the crack tip as the fatigue damage main contributor 8 . The numerical model, based on node releases, was firstly developed to predict the plastic Crack Tip Open Displacement (CTOD p ), which was related with FCGR to produce a crack growth law 9–13 . This parameter proved to be a measure of the crack tip plastic deformation 14 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…On previous works, the authors obtained numerical results in good agreement with experimental data, considering the cyclic plastic strain at the crack tip as the fatigue damage main contributor 8 . The numerical model, based on node releases, was firstly developed to predict the plastic Crack Tip Open Displacement (CTOD p ), which was related with FCGR to produce a crack growth law 9–13 . This parameter proved to be a measure of the crack tip plastic deformation 14 .…”
Section: Introductionmentioning
confidence: 81%
“…8 The numerical model, based on node releases, was firstly developed to predict the plastic Crack Tip Open Displacement (CTOD p ), which was related with FCGR to produce a crack growth law. [9][10][11][12][13] This parameter proved to be a measure of the crack tip plastic deformation. 14 Additionally, the results shown that crack closure is a fundamental mechanism concerning FCG.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the multidependent character of the fatigue crack growth process with respect to a large variety of variables and factors (variability of the material, loading, geometry, temperature, etc. ), current methods resort to the use of safety factors as a conservative approach, or by means of stochastic analysis, such as the proposal of Prates et al [8]. The authors perform a sensitivity analysis of the fatigue crack growth process based on numerical simulations, with respect to different factors (influence of material parameters and loading variability) in order to quantify their effects, in terms of the variability of the plastic CTOD.…”
Section: Fatigue Topicsmentioning
confidence: 99%
“…Marques et al [20] calculated ∆CTOD pl and ∆CTOD el for several instances using the finite element method and established a simple criterion that defines the boundary of the small-scale yielding (SSY) region to avoid the ineffective use of the LEFM parameter ∆K as a characterization parameter for the fatigue crack expansion rate. Andre Prates et al [21] conducted a numerical study of the effect of material parameters and load variability on plastic CTOD results and established a relationship between the most influential parameters and the range of plastic CTOD.…”
Section: Introductionmentioning
confidence: 99%